2020
DOI: 10.1186/s43094-020-00078-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic, antidyslipidemic, and antioxidant activities of methanol extract of Struchium sparganophora leaves in alloxan-induced oxidative stress-mediated diabetes in rats

Abstract: Background Diabetes mellitus is clinically underlined by hyperglycemia and dyslipidemia. In view of this, the current study assessed the glycemic and lipidemic control potentials of methanol extract of Sruchium sparganophora leaves (SPA) in the alloxan-induced diabetic model using male Wistar rats. Experimental diabetes was induced through a single intraperitoneal injection of 120 mg/kg freshly prepared alloxan. Thirty-six rats were randomly assigned into six groups of normoglycemic control, untreated diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It is a branched and fibrous water plant that is consumed as a leafy vegetable in soups among the occupants of the rural areas of Nigeria. The nutritive, phytochemical, antioxidant, antimicrobial and antimalarial properties of the leaves have been reported [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It is a branched and fibrous water plant that is consumed as a leafy vegetable in soups among the occupants of the rural areas of Nigeria. The nutritive, phytochemical, antioxidant, antimicrobial and antimalarial properties of the leaves have been reported [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of vegetablerich diets provides dietary fiber, phenolic antioxidants, and low calories important in combating diabetes mellitus and obesity. 41 The contrast in body weight changes with that reported in the work of Pupim et al, 40 may be linked to differences in the duration of the study. Earlier studies reported that hyperglycemia and hyperlipidemia characterized alloxan-induced diabetes in rats.…”
Section: Resultsmentioning
confidence: 83%
“…Oxidative stress is a major contributor to several pathological conditions, including cardiovascular disease, diabetes mellitus, cancer, rheumatoid arthritis, Alzheimer's disease, aging, atherosclerosis, etc. 2,3,4,5,6 It develops when ROS levels overwhelm endogenous antioxidant defense. Increased evidence from research investigations implicates oxidative stress as a significant pathogenic index for diabetes mellitus.…”
mentioning
confidence: 99%